Bargaining or Searching for a Better Price? - An Experimental Study - Francesco Feri; Anita Gantner (University of Innsbruck, Department of Public Finance, 2010)
This experimental study investigates two bargaining games with twosided incomplete information between a seller and a buyer. In the first game with no outside options many subjects do not use the incomplete information to their advantage as predicted. We find that a model with adjusting priors better explains observed behavior. The second game gives the buyer the option to buy via search or return to bargaining. Here many buyers choose a bargaining agreement when a search outcome is predicted. For those who opt out, search outcomes are overall efficient and behavior is relatively close to the optimal search policy.
Keywords: C91; C78; D83; D82; 330; Bargaining Experiment; Outside Option; Search; Verhandlungstheorie; Unvollkommene Information; Spieltheorie; Test; Theorie